IMPLEMENTASI ASAS TRANSPARANSI DAN PARTISIPATIF DALAM PENGELOLAAN DANA DESA: STUDI KASUS PADA DESA SEPAKUNG KABUPATEN SEMARANG - Dwi Diva Israny Matana; Aprina Nugrahesthy Sulistya Hapsari (Unitri Press, 2021)
The purpose of this study is to provide an evaluation related to the implementation of transparency and participatory principles in the management of Village Funds in Sepakung Village, Banyubiru District, Semarang Regency. This research is a qualitative descriptive study, where the data sources were obtained through in-depth interviews with resource persons involved in the management of the Village Fund. The analysis technique used is data reduction, triangulation, data presentation, and drawing conclusions. The results show that in general the Sepakung Government has implemented Village Fund management in accordance with two principles, namely in Permendagri Number 20 of 2018 which is carried out in a transparent and participatory manner although some in its implementation there are still obstacles both in document access and the existence of old documents that have been not updated, resulting in obstruction of community access to information on village fund management. So it is hoped that this research can provide benefits and evaluations for Sepakung Village regarding the implementation of transparency and participatory principles in the management of Village Funds.